2023
DOI: 10.1021/acsmaterialslett.3c00938
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Eutectogels as Electrodes for Underwater Electromyography Recording

Jon López de Lacalle,
Matias L. Picchio,
Antonio Dominguez-Alfaro
et al.

Abstract: Underwater recording remains a critical challenge in bioelectronics because traditional flexible electrodes can not fulfill essential requirements such as stability and steady conductivity in aquatic environments. Herein, we show the use of elastic gels made of hydrophobic natural eutectic solvents as water-resistant electrodes. These eutectogels are designed with tailorable mechanical properties via one-step photopolymerization of acrylic monomers in different eutectic mixtures composed of fatty acids and men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Under the interaction of DMF, the polymer network underwent continuous swelling until it was fully dissolved in the solvent. The eutectogel can be obtained again by evaporating the solvent through the casting method, which is a feature that distinguishes them from most of the eutectogels that have been reported to be obtained directly by photopolymerization. ,, Furthermore, for the dilemma of e-waste pollution and recycling difficulties, the eutectogel prepared in this article provides a feasible path for the future sustainable development of electronic devices.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Under the interaction of DMF, the polymer network underwent continuous swelling until it was fully dissolved in the solvent. The eutectogel can be obtained again by evaporating the solvent through the casting method, which is a feature that distinguishes them from most of the eutectogels that have been reported to be obtained directly by photopolymerization. ,, Furthermore, for the dilemma of e-waste pollution and recycling difficulties, the eutectogel prepared in this article provides a feasible path for the future sustainable development of electronic devices.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, researchers have now developed a variety of functional eutectogels based on DES systems, but most of them are based on hydrophilic systems. Considering the disadvantages of the water sensitivity of conventional hydrophilic eutectogels, researchers have developed hydrophobic eutectogels. For example, Fan and co-workers developed hydrophobic eutectogels with stretchable, underwater self-adhesive and sensing properties by one-step copolymerization of two monomers in hydrophobic DES, and Mecerreyes’ group reported elastic eutectogels using acrylic monomers in a eutectic solvent system consisting of fatty acids and menthol, and employed them for underwater electromyography recording. Although the hydrophobic eutectogels prepared in the above studies showed comprehensive performance, the recyclability was not addressed, which is important for the sustainable development of polymeric materials.…”
Section: Introductionmentioning
confidence: 99%
“…An important advantage of their application for biomedical purposes is their good underwater adhesion, but this can be decreased by the material's swelling and the formation of a water molecular layer on the surface of the hydrogel [56]. In this area, some eutectogels have also been tested as a potential material for underwater electrodes [59].…”
Section: Biomaterials and Othersmentioning
confidence: 99%
“…[64][65][66] In addition, some recent works have proposed eutectogels from therapeutic deep eutectic solvents (THEDES), where at least one component is an active pharmaceutical ingredient. [67][68][69][70] There is still much to be done in this emerging topic, principally expanding the application of eutectogels to other areas.…”
Section: Enzyme Immobilization In Eutectogelsmentioning
confidence: 99%